The invisible brand : marketing in the age of automation, big data, and machine learning - Ammerman, William, 1967- (McGraw-Hill, 2019)
"Marketers are harnessing the enormous power of AI to drive unprecedented results. The world of marketing is undergoing major change. Sophisticated algorithms can test billions of marketing messages and measure results, and shift the weight of campaigns, all in real time. What's next? A complete transformation of marketing as we know it, where machines themselves design and implement customized advertising tactics at virtually every point of digital contact. The Invisible Brand provides an in-depth exploration of the risks and rewards of this epochal shift, while delivering the information and insight you need to stay ahead of the game. Renowned technologist William Ammerman draws from his decades of experience at the forefront of digital marketing to provide a roadmap to our data-driven future. You'll learn how data and AI will forge a new level of persuasiveness and influence for reshaping consumers' buying decisions. You'll understand the technology behind these changes and see how it is already at work in digital assistants, recommendation engines and digital advertising. And you'll find unmatched insight into how to harness the power of artificial intelligence for maximum results. As we enter the age of mass customization of messaging, power and influence will go to those who know the consumer best. Whether you are a marketing executive or concerned citizen, The Invisible Brand provides everything you need to understand how brands are harnessing the extraordinary amounts of data at their disposal--and capitalizing on it with AI"--